ANALYSIS OF THE INFLUENCE OF THE COVID-19 PANDEMIC ON MANAGERIAL OWNERSHIP AND DIVIDEND POLICY IN INDONESIA: LITERATURE REVIEW - Putri, Eka Mutiara; Martono, Samuel (Manager : Jurnal Ilmu Manajemen, 2024)
This article examines the impact of the crisis due to the Covid-19 pandemic and managerial ownership on dividend policy. The purpose of writing this article is to analyze existing theories by comparing existing theories in several previous articles in the research literature. The literature review used is literature from reviews and journals that are related and appropriate to national and international financial management. All articles used come from Mendeley and Google Scholar literacy data. The reason for conducting qualitative research is because qualitative research has an exploratory nature. Next, an in-depth discussion was carried out and linked to the literature review which had been reviewed as a basis for formulating a hypothesis, then continued by comparing it with the results of previous research findings to reveal the truth of the existing theory. The method used in this research is a Systematic Literature Review or SLR which contains a description of theoretical findings and other research materials regarding dividend policy and managerial ownership during the Covid-19 pandemic. The results of this research are that companies tend to increase dividend distribution during the crisis caused by the pandemic in an effort to provide a positive signal to investors and support trading conditions in the capital market. Apart from that, the company also maintains the dividend level as a strategy to maintain investor confidence and the stability of the company's operations. Factors such as profitability and previous year's dividends have also been proven to have a positive influence on a company's dividend policy during crisis conditions. These findings provide important contributions for practitioners, academics, and further analysis in understanding the impact of the pandemic on company dividend policies as well as the importance of dividend policy strategies that are adaptive and responsive to unexpected external conditions.